2019
DOI: 10.3390/ani9060329
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Competence of Domestic Cat Vitrified Oocytes in 3D Enriched Culture Conditions

Abstract: Cryoinjuries severely affect the competence of vitrified oocytes (VOs) to develop into embryos after warming. The use of culture conditions that provide physical and chemical support and resemble the in vivo microenvironment in which oocytes develop, such as 3D scaffolds and coculture systems, might be useful to improve VOs outcomes. In this study, an enriched culture system of 3D barium alginate microcapsules was employed for the in vitro embryo production of domestic cat VOs. Cryotop vitrified-warmed oocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 64 publications
2
22
0
Order By: Relevance
“…Trying to restore VOs impaired competence, the combination of physical (presence of companion cells) and chemical (intercellular signalling) factors in the form of co-culture systems has been tested in different species with variable results (Attanasio et al, 2010;Casillas, Ducolomb, Lemus, Cuello, & Betancourt, 2015;Casillas et al, 2014). In our last study, an enriched culture system comprising a 3D environment (barium alginate microcapsules) and a co-culture with companion COCs gave some possibilities for domestic cat VOs development (Colombo, Morselli, Tavares, Apparicio, & Luvoni, 2019). Inspired by these results and convinced of the advantages given by the combination of physical and chemical factors in in vitro microenvironments, a 3D follicle-like structure was applied.…”
Section: Discussionmentioning
confidence: 99%
“…Trying to restore VOs impaired competence, the combination of physical (presence of companion cells) and chemical (intercellular signalling) factors in the form of co-culture systems has been tested in different species with variable results (Attanasio et al, 2010;Casillas, Ducolomb, Lemus, Cuello, & Betancourt, 2015;Casillas et al, 2014). In our last study, an enriched culture system comprising a 3D environment (barium alginate microcapsules) and a co-culture with companion COCs gave some possibilities for domestic cat VOs development (Colombo, Morselli, Tavares, Apparicio, & Luvoni, 2019). Inspired by these results and convinced of the advantages given by the combination of physical and chemical factors in in vitro microenvironments, a 3D follicle-like structure was applied.…”
Section: Discussionmentioning
confidence: 99%
“…biomaterial has also been reported for oocyte IVM [15,[32][33][34][35][36]. The clinical interest in IVM is constantly urged by the World Health Organization since infertility affects about 15% of couples [15].…”
Section: Plos Onementioning
confidence: 99%
“…COC-microbeads and assessing its validity on oocyte nuclear and cytoplasmic maturation. Indeed, most of the studies published to date described two-step or manual procedures [32][33][34][35][36]. Dorati et al [15] described alginate microbead preparation by the diffusion setting gelation technique in which, using a mouth-controlled hand-pulled glass Pasteur micro-pipette, single COCs were transferred into the alginate solution in culture medium and dropped into single wells of a 96-well plate containing the cross-linking agent.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Data from mouse and human studies have shown that vitrification better protects oocytes from structural damage and sustains gametes' developmental competence than slow freezing 12,14 . For the domestic cat, although both slow-freezing and vitrification have been used to preserve immature oocytes 4,13,15,16 , the rates of cryopreserved immature oocytes that complete nuclear maturation are much lower than for fresh gametes (0-38%) 3,4,13,16,17 . Different approaches have been used to improve the survival and developmental competence of mature and immature vitrified oocytes.…”
mentioning
confidence: 99%